Artificial Intelligence in Human Resource Management - Urh, Marko; Jereb, Eva (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
The use of artificial intelligence is growing rapidly and brings many benefits and improvements in human resource management. Despite the great interest in the use of artificial intelligence in human resource management, there is still a lot of doubts related to its use, long-term impact on employees, connectivity with existing systems, transparency, legal aspects, ethical use, and other elements. The paper shows some possibilities for using artificial intelligence in planning and recruitment, training and development, general administration, ethical aspects, and others. The advantages and disadvantages of using artificial intelligence in human resource management are also presented. The fact is that artificial intelligence will radically change the way of work, so the paper aims to explain the potential of artificial intelligence and present many other aspects and trends related to the mentioned concepts.